Corporate resilience : risk, sustainability and future crises - Seifi, Shahla; Crowther, David (Developments in corporate governance and responsibility, 2023)
The world has gone through profound change since 2019, which has impacted economies, organisations, societies, and ways of working. Now, more than ever, businesses need to be prepared and resilient to large-scale changes. Written by experts, the chapters collected here address various issues such as climate change and the pandemic, suggesting ways in which future crises can be managed successfully and sharing best practice from what we have learned from recent crises. The globally diverse authorship in Corporate Resilience brings together a range of perspectives on corporate resilience and crisis management from varying industries to explore this topic in great depth. Areas studied range from building global resilience through sustainable development and social responsibility, to corporate resilience, environmental investment, internet financial reporting and reporting on human rights. Developments in Corporate Governance and Responsibility offers the latest research on topical issues international experts and has practical relevance to business managers.